Indicators Analysis of Scope Creep Causation Factors in Indonesian Offshore Oil & Gas Construction Projects - Perdana, Adhitya; Wiguna, I Putu Artama (Faculty of Engineering, Universitas Swadaya Gunung Jati, 2024)
The Indonesian oil and gas (O&G) industry, a strategic sector with vast offshore reserves, faces significant challenges due to the high failure rate of offshore construction projects. This profusion of offshore reserves has led to a rise in offshore O&G construction projects. However, the global failure rate of O&G offshore construction projects is alarming, with numerous projects experiencing delays, budget overruns, and quality issues that hinder the achievement of production targets. Scope creep, a common phenomenon leading to delays, cost overruns, and quality issues, is a major contributor to these failures. To address this critical problem, this study aims to develop and validate measurement indicators for the causative factors of scope creep in Indonesian offshore O&G construction projects. A quantitative research approach was employed, combining literature review, pilot survey, and a main survey involving 104 practitioners in the industry. Data analysis using SmartPLS 3.0 confirmed the validity, reliability, and outer loading value of measurement indicators. Key findings reveal that risk consequences and awareness are crucial indicators of the risk factor, communication frequency is a key indicator for the communication factor, task overlap and knowledge diversity are identified as key indicators of complexity, construction method changes are a key contributor to the change factor, and accurate identification and structuring of decomposed project tasks are critical indicators for achieving desirable quality in Work Breakdown Structure development. These findings provide valuable insights for industry professionals to mitigate scope creep and improve the success of offshore O&G construction projects in Indonesia. Key words: Scope creep, Project Management, Project Scope Management, Offshore Construction Projects, Oil and Gas.